Probabilistic kingdom – problem of objectivity in contemporary science - Pruski, Paweł (Humaniora. Czasopismo Internetowe, 2020)
Within the world of modern scientific theories, probability theory is one of the basic tools with which hypotheses are constructed. Scientists using probability theory often rely on its objective interpretation. In practice, this means that probability assertions should be independent of the beliefs of the individual. Accordingly, the following question arises: what do the contents of scientific assertions based on an objective interpretation of probability theory refer to? To answer that question, the author analyzes objective probability in the context of the scientific debate on determinism, addressing two types of arguments. On the one hand, a position will be examined according to which the only viable plane allowing for objective probability is indeterministic. Subsequently, the discussion will focus on arguments to the contrary, which presume coexistence of objective probability and determinism. The aim of this paper is to answer the question concerning the meaning of a sentence referring to the objective interpretation of probability, and aim to resolve whether it is in the context of either deterministic or indeterministic plane that one can speak of objective probability. As a result, the following thesis will be advanced: both the acceptance of a deterministic and an indeterministic plane as possible areas where objective probability can occur is extremely problematic. Depending on the chosen area, different types of problems arise, whose common denominator is misunderstood objectification. Consequently, the postulated objectivity of probability (and pertinent assumptions) can be reduced to the epistemic variant.